2020
DOI: 10.21831/economia.v16i1.30308
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Rotating Savings and Credit Associations (ROSCAs) and Poverty in Indonesia

Abstract: Arisan or Rotating Savings and Credit Associations (ROSCAs) constitute one of the most commonly found informal financial institutions in the developing world. This study aims to analyze the effect of Rotating Savings And Credit Associations (ROSCAs) on poverty in Indonesia using panel data sourced from the fourth and fifth wave of the Family Life Survey (IFLS). This study used a conditional logit or fixed effect logit to see the effect of Rotating Savings and Credit Associations (ROSCAs) participation and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The results in Table 5 show that participation in arisan (ROSCAs) is proven to be able to reduce the level of poverty in Indonesia. The results of this study are supported by the research by Kharisma et al (2020) showing that arisan can be used as a tool to reduce poverty levels. Individuals or households can use the money earned from arisan (ROSCAs) for various purposes, such as adding assets, expanding business capital, etc.…”
Section: Resultssupporting
confidence: 77%
“…The results in Table 5 show that participation in arisan (ROSCAs) is proven to be able to reduce the level of poverty in Indonesia. The results of this study are supported by the research by Kharisma et al (2020) showing that arisan can be used as a tool to reduce poverty levels. Individuals or households can use the money earned from arisan (ROSCAs) for various purposes, such as adding assets, expanding business capital, etc.…”
Section: Resultssupporting
confidence: 77%
“…There is a form of social gathering and microfinance for communities through rotating savings that have long been a part of the socio-economic culture amongst communities. The rotating savings and credit associations, arisan , are the most popular informal associations in Indonesia for mutual savings (Kharisma et al, 2020). Like arisan in various ways, a waste bank is also a platform for social gatherings at the community level.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the approach used in previous research, this study uses a consistent approach to isolate all observed and unobservable determinants of village meeting. Vanadharajan's [23] research used IFLS-2 (1997) cross-section data, while Lasagni and Lollo [24] used IFLS-3 (2000) and IFLS-4 (2007). The two studies on village meeting in Indonesia did not anticipate the possibility of an unobserved factor effect that could potentially produce a biased estimator.…”
Section: Discussionmentioning
confidence: 99%